Mesenchymal Stem Cells Improve Cognitive Impairment and Reduce Aβ Deposition via Promoting AQP4 Polarity and Relieving Neuroinflammation in Rats With Chronic Hypertension-Induced Cerebral Small-Vessel Disease - Liu, Xiao lu; Ouyang, Fu bing; Hu, Liu ting; Sun, Pei; Yang, Jing; Sun, Yuan jing; Liao, Meng shi; Lan, Lin fang; Pei, Zhong; Fan, Yu hua (Frontiers in Aging Neuroscience, 2022)
Cerebral small-vessel disease (CSVD) is the main cause of vascular cognitive impairment (VCI), and the accumulation of amyloid β-protein (Aβ) may be significantly involved in CSVD-induced VCI. The imbalance between Aβ production and clearance is believed to be an important pathological mechanism of Aβ deposition in Alzheimer disease. In this study, we aimed to disclose the roles of aquaporin 4 (AQP4) and neuroinflammation in CSVD, which were the key factors for Aβ clearance and production, respectively, and the effect of mesenchymal stem cells (MSCs) on Aβ deposition and these two factors. The stroke-prone renovascular hypertensive (RHRSP) rats were grouped and received MSC and MSC + AS1517499 (an inhibitor of pSTAT6). The latter was used to explore the underlying mechanism. The cognitive function, white matter lesions, Aβ expression, expression, and polarity of AQP4, neuroinflammation and the STAT6 pathway were investigated. Compared with sham-operated rats, RHRSP rats showed spatial cognitive impairment, white matter lesions and Aβ deposition. Moreover, AQP4 polarity disorder and neuroinflammatory activation were found, which were linked to Aβ deposition. Treatment with MSCs markedly improved cognitive tasks and reduced Aβ deposition but failed to reduce white-matter lesions. Furthermore, MSCs not only promoted AQP4 polarity but also alleviated neuroinflammation probably through the STAT6 pathway. The present study demonstrated that Aβ deposition, AQP4 polarity disorder and neuroinflammation might be involved in CSVD and the regulatory effects of MSCs on them suggested potential therapeutic value for CSVD.